2020
DOI: 10.1111/clr.13584
|View full text |Cite
|
Sign up to set email alerts
|

Changes of radiopacity around implants of different lengths: Five‐year follow‐up data of a randomized clinical trial

Abstract: Objective To follow‐up the radiographic changes in peri‐implant bone of short (6 mm, test group) and long (10 mm, control group) single‐unit implants five years after loading. Materials and methods Forty‐three implants of the test and 44 implants of the control group could be reassessed from 96 originally included implants. Standardized areas of interest (AOI) were defined in the peri‐implant bone at pre‐defined locations at mid‐length on both sides of the implants, and at the apex. An arbitrary mean grey scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…24,34 It has been found that the bone around short implants might F I G U R E 5 Median gray-scale values (GSV) of implants in the mandible that survived and the implants that failed at different time points become denser in response to the load. 25,29,35 This phenomenon was confirmed in the present study, where the radiographic density increased over time after implant loading in both groups.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…24,34 It has been found that the bone around short implants might F I G U R E 5 Median gray-scale values (GSV) of implants in the mandible that survived and the implants that failed at different time points become denser in response to the load. 25,29,35 This phenomenon was confirmed in the present study, where the radiographic density increased over time after implant loading in both groups.…”
Section: Discussionsupporting
confidence: 87%
“…Depending on the intensity and the direction of the load, the peri‐implant bone responds through up or downregulating bone metabolism 24,34 . It has been found that the bone around short implants might become denser in response to the load 25,29,35 . This phenomenon was confirmed in the present study, where the radiographic density increased over time after implant loading in both groups.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings are in agreement with a recent published RCT, reporting a difference of 0.41 mm even if at a follow-up of 1 year and with 5.5-mm short implants. 6 Furthermore, the better bone stability around short implants could be explained by a recent study 13 in which longer implants showed a slightly stronger change of radiopacity of the periimplant bone than short ones after five years of loading.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the morbidity risks related to the surgical interventions, a parallel arm of research on short implants is currently on-going [13][14][15]. In their recent clinical report, Naenni et al highlighted how the use of implants of 6 mm length did not show significant differences in survival rate and peri-implant marginal bone loss compared to implants of 10 mm length [15].…”
Section: Introductionmentioning
confidence: 99%